Rapid Competitive Immunochromatographic Assay For The Detection Of Tetrahydrocannabinol In Human Urine (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: Cannabis is among the earliest mind-altering drugs known to man and has been around for at least 4000 years. Today it is world’s most commonly used illicit drug, with more than 300 million regular users. The aim of the study is detection of tetrahydrocannabinol (THC) in urine using immunochromatographic assay- a qualitative method.Materials and method: Retrospective study was done based on the report of urine tests conducted in the Dept. of Forensic Medicine in one year from July 2022 to June 2023. Consent from the individual brought for examination by the police.Results and Conclusion: Total 118 cases were studied; all were males among which 93 were positive and 25 negative. It is a preliminary screening test for cannabis substance abuse which will help the Police for further investigation.
Keywords: Cannabis, tetrahydrocannabinol(THC), immunochromatographic assay, qualitative method.